Penerapan Kepatuhan Standardisasi Sertifikasi Halal pada UMKM di Kecamatan Telanai Pura - Algian fahrozi; Arsa Arsa; Achyat Budianto (Lembaga Yasin AlSys, 2026)
The issue of halal certification for micro, small, and medium enterprises (MSMEs) has become increasingly important in response to the growing demand for assurance of product halalness; however, studies examining business actors’ compliance after obtaining halal certification remain relatively limited. This study aimed to analyze the level of compliance among MSME actors in Telanai Pura Subdistrict, Jambi City, in implementing halal certification standards and to identify the obstacles they faced. The study employed a qualitative approach with a descriptive design. Informants were selected through purposive sampling from food MSME actors who had already obtained halal certification. Data were collected through interviews, observation, and documentation and were analyzed using the Miles and Huberman model. The findings showed that MSME actors generally demonstrated a fairly strong level of awareness and commitment in implementing halal principles, as reflected in their efforts to maintain raw materials, production processes, and internal supervision. However, this level of compliance was not yet fully optimal because they still faced several constraints, including limited financial resources, low employee understanding, inconsistent use of personal protective equipment, and difficulties in obtaining certain raw materials. These findings underscore that halal certification should not be understood merely as an administrative requirement, but must be accompanied by stronger internal systems, continuous guidance, and consistent supervision so that the implementation of halal standardization can be carried out more effectively.